Balancing the charge: the evolution of battery active equalizers in shaping a sustainable energy storage future - Rovianto, Eki; Khairunnisa, Khairunnisa; Lenggana, Bhre Wangsa; Fardan, Muhammad Faris; Harsito, Catur; Prasetyo, Ari (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
As the world embraces sustainable energy solutions, energy storage systems are becoming increasingly critical for the effectiveness of renewable energy sources. Batteries have emerged as a promising option. However, to fully harness the potential of batteries, the challenge of cell must be overcome. This review article delves into the evolution of battery active equalizers on the quest for sustainable energy storage solutions. The review begins by exploring the fundamental principles of battery active equalization and its significance in optimizing energy storage system performance and efficiency. Traditional battery management techniques are limited in their ability to address imbalances effectively, making active equalization a compelling alternative. The review provides a comprehensive analysis of early developments and current state-of-the-art active equalization systems. The reviewed article demonstrates successful applications, showcasing how active equalizers can significantly improve energy storage performance and overall system stability. While active equalization offers tremendous promise, it is not without challenges. The review explores how these technologies seamlessly fit with renewable energy sources and grid systems, opening up possibilities for future energy infrastructure. Industry perspectives play a vital role in realizing innovative technologies. Therefore, the review incorporates insights from leading experts, presenting their viewpoints on the adoption of battery active equalizers.